Laboratory and field observations in emergency relief work in a city in Eastern India - Bhattacharyya, Sayan; Nandy, Bibhas; Chandra, Ramesh; Das, Papiya (Eastern Journal of Medical Sciences, 2020)
Microbiology laboratories must be well prepared to tackle outbreaks in disasters such as waterlogging and flood. Laboratories must be well equipped and prepared to identify the diseases such as dengue and other arboviral diseases, diarrhea, and skin infections. We, as a central team, assessed the laboratory preparedness in a city affected by flood and waterlogging by personal visits and records. It was noted that referral and other government laboratories were performing the recommended tests for arboviral diseases, along with tests for leptospirosis and scrub typhus. We conclude that an all-round effort by multidisciplinary workers with money and adequate workforce is required for early and proper laboratory diagnosis of infections in such scenario.